POTRET KEHIDUPAN LESBIAN KOTA PEKANBARU - Arsita, Desi; Razif, M. (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Lesbians are women who have sex with same-sex love, or commonly referred to homosexual women the emotional relationship that involves love and affection of two men who had sex at the both women. Background this study caused because many women were in a relationship with a woman in a loving relationship that is serious in dating status in Pekanbaru city, but human nature created in pairs. This study aims to investigate the characteristics of lesbians in Pekanbaru city in this case the researchers start with the data in depth informant, lesbian characteristics according to age, education level, religion, ethnicity, labels in the community, and how to distinguish heterokseksual lesbian women, whose activities are often carried out lesbians This collective group of lesbians in Pekanbaru and activities that are often done as a couple lesbinya lesbians at home and outside the home and the factors that cause a person become lesbians. In this study the respondents amounted to ten people from the community KBBP (Large Family Belog Pekanbaru), respondents came from various backgrounds ranging from students to students. Data collection was done by observation study in which researchers took direct participation in the lives of the respondents either at home or in the lesbian community as well as in-depth interviews to the respondents. From the findings of the field can be seen that in terms of age is still old lesbians 15 years to 22 years, the average has a very good education, the majority religion of Islam and the five respondent is a native of Soweto and five other people are migrants, the majority of ethnic Malay and Minang, six respondents in this study is the butch and femme four people are. The cause of these respondents into lesbianism caused because the four-person family unfavorable influence, fourJom FISIP Volume 1 No. 2 – Oktober 2014 2more people because the influence of the environment and the wrong friends thatwent along with trying to be a lesbian, the rest of the respondents were two otherscaused because the desire itself that is being hurt because of trauma factorbecause the former lover and want to be faithful to his male lover who had died.Keywords: Lesbian, Potrait, Sexual Deviations